2020
DOI: 10.1177/0265407520970645
|View full text |Cite
|
Sign up to set email alerts
|

Suspicion about a partner’s deception and trust as roots of relational uncertainty during the post-deployment transition

Abstract: Relational uncertainty is both prominent and pivotal during the transition from deployment to reintegration. Most prior research has considered the outcomes rather than the origins of relational uncertainty, hampering the development of interventions for military couples. We theorize about two predictors of relational uncertainty during the post-deployment transition: suspicion about a partner’s deception and trust. Results of an 8-wave longitudinal study involving 287 U.S. military couples ( N = 4,147 observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…We opted, then, for a particularly stringent test by covarying relationship quality when predicting sequences of self-disclosure/hostility and validation/hostility. By demonstrating an association between relational uncertainty and dyadic asynchrony above and beyond relationship quality ( H1 , H2 ), our findings not only rule out a potential confound, but also contribute to a growing body of evidence differentiating relational uncertainty and relationship quality (e.g., Knobloch et al, 2021; Knobloch & Theiss, 2017).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We opted, then, for a particularly stringent test by covarying relationship quality when predicting sequences of self-disclosure/hostility and validation/hostility. By demonstrating an association between relational uncertainty and dyadic asynchrony above and beyond relationship quality ( H1 , H2 ), our findings not only rule out a potential confound, but also contribute to a growing body of evidence differentiating relational uncertainty and relationship quality (e.g., Knobloch et al, 2021; Knobloch & Theiss, 2017).…”
Section: Discussionsupporting
confidence: 60%
“…People tend to be less satisfied with their relationship under conditions of relational uncertainty (e.g., Goodboy et al, 2020), and in interaction, individuals experiencing relationship distress tend to exhibit more negative behaviors (e.g., hostility, criticism, blame, defensiveness, withdrawal) and less positive behaviors (e.g., approval, empathy, affection; for review, see Balderrama-Durbin et al, 2020). Guided by research showing divergence between relational uncertainty and relationship quality as predictors of communication behavior (e.g., Knobloch et al, 2021; Knobloch & Theiss, 2017), we expect that relational uncertainty is negatively associated with dyadic synchrony over and above people’s reports of relationship quality. Formally stated:After covarying relationship quality, relational uncertainty corresponds with less dyadic synchrony via more frequent behavioral sequences of self-disclosure/hostility (H1) and validation/hostility (H2).…”
Section: Dyadic Synchrony Within Interactionmentioning
confidence: 99%
“…, 2016). Research also revealed that the length of time at home is positively associated with relational uncertainty, interference from partners and relationship dissatisfaction (Knobloch and Theiss, 2011, 2014; Knobloch et al. , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Elliott, 2015; Heinecken and Wilén, 2019; Knobloch et al. , 2019; Knobloch et al. , 2020; Knobloch and Theiss, 2011; Knobloch and Theiss, 2014; Knobloch and Theiss, 2018; Milliken et al.…”
Section: Discussionmentioning
confidence: 99%